Efforts to Increase Knowledge of Pregnant Women About Stunting Prevention Through Health Education in Karangmekar Village, Working Area of Central Cimahi Health Center - Sri Wulandari Novianti; Siti Laela Saida W (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims : This study aims to identify changes in pregnant women's knowledge about stunting prevention through health education in the Karangmekar Subdistrict, the working area of the Central Cimahi Health Center, by modifying health education media. Method : The research method used a pre-experiment with a group pre-post-test design, with a sampling technique was a total sampling of 33 pregnant women respondents. Data analysis used the marginal homogeneity test. Result : The results of the univariate analysis showed that before health education, the level of knowledge of pregnant women about stunting prevention was 51.5% in the poor category, and after health education was 75.8% in the good category. The results of the bivariate analysis showed that there was an increase in pregnant women's knowledge about stunting prevention through health education with a p-Value (0.000) < α (0.05). Conclusion : Pregnant women's knowledge about stunting prevention increased significantly before and after health education in Karangmekar Village, Cimahi Health Center work area. The choice of media as a learning aid affects the material presented, making it necessary to develop a sustainable health education program with modifications to learning media.